(untitled) (UNED Research Journal, 2016)
In the last decade the importance of social participation in the development of conservation projects in Latin America has become obvious. In Costa Rica, Caiman crocodilus is an important species in the Caño Negro Wildlife Refuge. To make an analysis of the social and economic standing of the community, in August 2013 I organized two workshops with 15 people interested in breeding the species. Even if there is a market interested in the skin, breeding would not be pro table and would have to be subsidized in the first six years. Additionally, the project is not feasible because of ignorance about the species, lack of resources, poor integration of social actors, low management capacity and weak linkages with government institutions and NGOs.